A Phase 3 Study to Evaluate the 1-Year Efficacy and Safety of Udenafil 75 mg Once Daily in Patients with Erectile Dysfunction. Issue 8 (1st August 2016) - Moon, Ki Hak; Kim, Sae Woong; Moon, Du Geon; Kim, Je Jong; Park, Nam Cheol; Lee, Sung Won; Paick, Jae-Seung; Ahn, Tai Young; Chung, Woo Sik; Min, Kwon Sik; Park, Jong Kwan; Yang, Dae Yul; et al.
ABSTRACT: Introduction: Once-daily administration of phosphodiesterase type 5 inhibitors has been shown to correct erectile dysfunction (ED). Aim: To evaluate the long-term efficacy and safety after once-daily oral administration of udenafil 75 mg in men with ED. Methods: This clinical trial was an open-label, fixed-dose, 24-week extension study (DA8159_EDDL_III) of a 24-week double-blinded efficacy and safety study of once-daily udenafil (parent study: DA8159_EDD_III). Subjects received udenafil 75 mg once daily for 24 weeks during this extension study, and the follow-up visit occurred during the 4-week ED treatment-free period. Main Outcome Measures: Subjects were asked to complete the International Index of Erectile Function questionnaire and the Global Assessment Questionnaire at the 24-week extension and after the 4-week ED treatment-free period, and the development of adverse drug reactions was investigated. Results: In total, 302 subjects were enrolled in this extension study. Improvement was shown with an increased erectile function (EF) domain score compared with baseline (14.60 ± 4.57) at extension week 48 (23.98 ± 5.44) and a slight increase in EF domain score compared with the last time point (week 24) of the parent study ( P < .001). The Global Assessment Questionnaire showed a high improvement rate of 95.4% at the extension 48-week time point. For shift to normal, almost half the subjects (45.1%) recovered "normal" EF, and 14.2% of subjects reported normal erections after the 4-week ED treatment-free period. The occurrence rate of adverse drug reactions was 8%, which consisted mainly of flushing and headache. Conclusion: Once-daily dosing of udenafil 75 mg showed excellent efficacy and safety with long-term administration and allowed a more spontaneous sexual life.